Severity and outcome assessments of patients undertaking surgical orthodontic treatment - Zhao Yilong; Fowler Peter V. (Sciendo, 2014)
Background: Combined orthognathic-orthodontic treatment can be lengthy and expensive. It is therefore important to evaluate the effectiveness of proposed treatment and the likely outcomes.